Potential early markers for breast cancer: a proteomic approach comparing saliva and serum samples in a pilot study - ARĞA, KAZIM YALÇIN (My University, 2023)
Breast cancer is the second leading cause of death for women in the United States, and early detection could offer patients the opportunity to receive early intervention. The current methods of diagnosis rely on mammograms and have relatively high rates of false positivity, causing anxiety in patients. We sought to identify protein markers in saliva and serum for early detection of breast cancer. A rigorous analysis was performed for individual saliva and serum samples from women without breast disease, and women diagnosed with benign or malignant breast disease, using isobaric tags for relative and absolute quantitation (iTRAQ) technique, and employing a random effects model. A total of 591 and 371 proteins were identified in saliva and serum samples from the same individuals, respectively. The differentially expressed proteins were mainly involved in exocytosis, secretion, immune response, neutrophil-mediated immunity and cytokine-mediated signaling pathway. Using a network biology approach, significantly expressed proteins in both biological fluids were evaluated for protein–protein interaction networks and further analyzed for these being potential biomarkers in breast cancer diagnosis and prognosis. Our systems approach illustrates a feasible platform for investigating the responsive proteomic profile in benign and malignant breast disease using saliva and serum from the same women.
Keywords: Bilgisayar Bilimleri; Kimya Mühendisliği ve Teknolojisi; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Computer Sciences; Chemical Engineering and Technology; Life Sciences; Molecular Biology and Genetics; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Bilgisayar Bilimi; Mühendislik; MÜHENDİSLİK, KİMYASAL; KİMYA, İNORGANİK VE NÜKLEER; SPEKTROSKOPİ; KİMYA, FİZİKSEL; KİMYA, ORGANİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); COMPUTER SCIENCE; ENGINEERING; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; ENGINEERING, CHEMICAL; CHEMISTRY, INORGANIC & NUCLEAR; SPECTROSCOPY; CHEMISTRY, PHYSICAL; CHEMISTRY, ORGANIC; Kataliz; Fizik Bilimleri; Moleküler Biyoloji; Bilgisayar Bilimi Uygulamaları; Fiziksel ve Teorik Kimya; Organik Kimya; İnorganik kimya; Catalysis; Physical Sciences; Molecular Biology; Computer Science Applications; Physical and Theoretical Chemistry; Organic Chemistry; benign; breast cancer; diagnostic; malignant; potential biomarkers; prognostic; protein–protein interaction network; proteomics; saliva; serum